The paradox of monetary profits: an obstacle to understanding financial and economic Crisis? - Charlotte Bruun; Carsten Heyn-Johnsen (Kiel Institute for the World Economy (IfW), 2009)
The paradox of monetary profits has been a recurrent theme in macroeconomics since the problem was first formulated by Marx. Capitalists as a whole can at most get from workers, what they already paid out in wages. Marx did not solve this problem, and neither did Keynes, who had to face the problem in “The General Theory”. A consequential logical conclusion to Keynes' treatment of the problem, leaves his concept of aggregate income indeterminate—based on imaginary magnitudes. Both Marx and Keynes tried to solve the problem by addressing current transaction flows, which is also the approach taken by more recent contributors. Another solution to the problem is to regard monetary profits as a flow arising from changes in stock magnitudes—more specifically the monetary valuation of real capital performed at financial markets. Besides solving the paradox of monetary profits, this solution also provides us with a very strong connection between the real and the financial spheres. The monetary profit inducing capitalist production, emanates from the sphere of finance. In a world of fundamental uncertainty this gives us an explanation of, not only what may drive financial booms and busts, but also how these movements on financial markets are related to the real sphere of production.
Keywords: E44; E01; G01; E11; E12; E25; 330; Monetary production theory; stock-flow consistency; finance; national income accounting; Kapitalertrag; Wertpapierhandel; Börsenumsatz; Finanzierung; Finanzmarkt; Volkswirtschaftliche Finanzierungsrechnung; Gesamtwirtschaftliche Produktionstheorie; Finanzmarktkrise; Wirtschaftskrise; Theorie